Hybrid-PjBL Model Integrating Local Wisdom, Scientific Curiosity, and Metacognitive Awareness: Content and Construct Validity - Fatmawati, Baiq; Calaminos, Franklin; Asy’ari, Muhmmad; Hunaepi, Hunaepi (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2026)
Procedural knowledge is an essential component of 21st-century science learning because it enables students to select, apply, and evaluate strategies for solving scientific problems. Project-Based Learning (PjBL) is widely recognized as a student-centered model for developing problem-solving, collaboration, and higher-order thinking skills; however, its implementation still requires stronger support for students’ learning regulation, motivation, and contextual scientific inquiry. This study examined the content validity, expert-based construct coherence, and reliability of a Hybrid Project-Based Learning (Hybrid-PjBL) model integrating local wisdom, scientific curiosity, and metacognitive awareness to support prospective science teachers’ procedural knowledge. This study represents the validation stage of a development research project. The developed model and its supporting tools, including semester learning plans (RPS), learning scenarios, modules, student worksheets (LKPD), and assessment instruments, were validated through a focus group discussion involving seven validators: four experts and three practitioners. Data were collected using validation sheets and analyzed descriptively using validity coefficients and reliability estimates. The results showed that the Hybrid-PjBL model was valid and reliable (rα = 0.76; α = 0.86). The supporting tools were also categorized as valid and reliable, including RPS (rα = 0.85; α = 0.92), learning scenarios (rα = 0.81; α = 0.89), modules (rα = 0.78; α = 0.88), LKPD (rα = 0.95; α = 0.97), and assessment instruments (rα = 0.88; α = 0.93). These findings indicate that the developed model and tools are appropriate for further practicality and effectiveness testing in real classroom settings